Case Report: Third eyelid flap for correction of proptosis-induced lateral strabismus in two dogs - Jeon, Byung-Ju; Kim, Joon-Young (Frontiers in Veterinary Science, 2025)
This case report describes the use of a third eyelid flap to correct proptosis-induced lateral strabismus in two dogs: a 3-year-old castrated male Pomeranian (Case 1) and a 2-year-old intact female Bichon Frise (Case 2). In both cases, the third eyelid was sutured to the dorsolateral conjunctiva using a horizontal mattress suture. However, conjunctival elongation at the suture site compromised flap function, necessitating reoperation. In Case 2, a second horizontal mattress suture was added to improve stability. Following reoperation, Case 1 achieved complete correction of lateral strabismus by day 42, with transient third eyelid protrusion and corneal thinning resolving within two weeks. In Case 2, mild residual strabismus remained, but cosmetic improvement was substantial, and third eyelid inflammation resolved similarly. These cases demonstrate the potential utility of a third eyelid flap as an adjunctive method for correcting lateral strabismus secondary to proptosis in dogs, offering a less invasive alternative to conventional incisional surgery.